Microbial control of whiteflies - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1994)
The whitefly, Bemisia tabaci, which is variously known as the cassava, cotton or tobacco whitefly, is a cosmopolitan pest attacking a wide range of arable, horticultural and ornamental crops. As well as causing direct damage through feeding, and...